Back to basics: sticky prices in the monetary transmission mechanism (2011)
I use the measures of frequency of price adjustment in Nakamura and Steinsson (2008) to show that stickier price industries have higher levels of output response to monetary policy shocks. Using a Vector Auto-regression model, I build different measures of response to a monetary policy shock of 14 US industries. These measures are shown to be related to the level of price rigidity. More precisely, I find that if firms within an industry change prices twice as often as firms in another industry, output deviation from trend in response to a negative shock of 25 basis points will be 69 percentage points smaller in the less sticky industry. This result is stronger when I account for measurement error in the level of response.